Recent developments in spectral-based ultrasonic tissue characterization - Coila A. (2018)
Echographic imaging depicts anatomical structure by displaying the magnitude of the envelope-detected backscattered echoes. However, ultrasonic radiofrequency data contains a richer information content that can be exploited for constructing images of intrinsic tissue properties. In particular, spectral-based ultrasonic tissue characterization techniques allow imaging parameters such as the backscatter coefficient and the attenuation coefficient. Even though this type of analysis has been explored for decades, several challenges ranging from technical algorithmic issues to the lack of widely validated, successful clinical applications have limited efforts directed towards these imaging modalities. In this article, recent developments are reviewed such as the use of plane wave compounding for improving imaging penetration, simultaneous estimation of backscatter coefficients and shear wave speed maps with potential to characterize kidney transplants, the use of the exponential form factor to model backscatter coefficients from tissues, and the use of regularized inversion methods for attenuation coefficient imaging in vivo. © 2018 IEEE.